Analysis of synthetic storm technique based on Ku-Band Satellite Beacon measurements in Malaysia - Lwas, Ali K.; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Ismail, Ahmad Faris; Singh, Mandeep; Chebil, Jalel; Zyoud, Al-Hareth; Dao, Hassan (Springer International Publishing Switzerland, 2015)
Most of the existing rain attenuation prediction models were proposed based on measurements taken in temperate climates. These models are found not accurate in tropical regions and were thus modified in order for such models to be applied in tropical regions. Synthetic Storm Technique (SST) is one of the most reliable methods to estimate rain attenuation time series in Europe. However, due to the lack of measured data in the tropical regions of the world, the above-mentioned method is yet to be validated for those regions. This paper aims to investigate SST validity in Malaysia by focusing on both rain events and the overall statistical behavior. Its performance is assessed based on concurrent measurement of Ku-band satellite beacon and rain rate over University of Science Malaysia (USM) campus at Tronoh. Preliminary analysis shows that SST is capable of providing details of time-series of many rain events to reflect the dynamics of rain fade. However, it is unable to predict the entire range of rain intensity.